Analysis of Plasma Farmers' Satisfaction Levels in the Implementation of Partnership with PT. Ciomas Adisatwa in Wonggeduku District, Konawe Regency - Maragi, Muh. Ikhawan Alif Al; Rianse, Ilma Sarimustaqiyma; Yusriadin (International journal of technology and education research, 2025)
This study aims to determine the level of satisfaction of plasma farmers with the implementation of the partnership program run by PT. Ciomas Adisatwa in Wonggeduku District, Konawe Regency. This partnership is expected to increase farmers' income. The research population consisted of all 8 plasma farmers in Wonggeduku District who collaborated with PT. Ciomas Adisatwa, and data collection was carried out using the census method. Primary data were obtained through interviews using questionnaires, while secondary data were sourced from the Central Statistics Agency (BPS) and relevant government agencies. Data analysis employed descriptive methods for partnership patterns and interval class calculations with a Likert scale for satisfaction levels. The results indicate that the overall satisfaction level of plasma farmers falls into the